PETROLOGY AND MINERALOGY OF LAVA OF PATUHA VOLCANO, BANDUNG, WEST JAVA - Rio
The characteristics of magma and the processes that occur inside the magma chamber are recorded in mineralogy, texture and the chemical composition of the rocks. The study was conducted on 6 units of andesite lava of Patuha Volcano to identify the petrology and mineralogy, magma characteristics (affinity, temperature, and pressure), and the magmatic evolution of Patuha Volcano. Fifteen samples were microscopically analyzed and 6 samples were used for mineral chemistry analysis using SEM-EDS that represent lava units of the research area. From old to young, the 6 lava units on the research area consist of Patuha Andesite Lava 1 (Pl1), Patuha Andesite Lava 2 (Pl2), Patuha Andesite Lava 3 (Pl3), Patuha Andesite Lava 4 (Pl4), Patuha Andesite Lava - Breccia Pyroclastic Flow 2 (Pa2), and Cimanggu Andesite Lava (Cil). Based on the calcic-clinopyroxene analysis, the magmatic affinity of Patuha Volcano was calc-alkaline that related to subduction process. The magmatic evolution was initiated by basaltic andesite composition of the magma with temperature was range 887-1102oC which was influenced by the injection of more primitive magma on Patuha Andesite Lava 1 (Pl1). The process of more primitive magma injection occurred more intensively resulting in an increase in temperature in the magma chamber to 1000-1030oC on Patuha Andesite Lava 2 (Pl2) and an increase in temperature in the magma chamber to 970-1050oC on Patuha Andesite Lava 3 (Pl3). Volcanism activity in the form of the differentiation process caused a decrease in temperature to 923-1000oC and affected the formation of Patuha Andesite Lava 4 (Pl4). Then the more primitive magma injection process played a role in increasing the temperature of magma chamber to 1050-1130oC on Patuha Andesite Lava - Breccia Pyroclastic Flow 2 (Pa2) and to 900-1062oC on Cimanggu Andesite Lava (Cil).